Penerapan Sosialisasi Digital Marketing Dan Pembuatan Marketplac Sebagai Upaya Peningkatan Penjualan Di Kelurahan Pakunden Dan Kelurahan Turi Kecamatan Sukorejo - Fani Khoirotunnisa; Izah Bana Murtazah; Sheni Nahla Syifani; Moch. Syahrir Sauki (Jurnal Pengabdian Kepada Masyarakat, 2023)
Technology has developed rapidly in the age of scientific progress. This is unavoidable because technology can provide positive benefits for developing product innovations. With the existence of technology, humans can use it as access to search for extensive information via the internet. Socialization of Digital Marketing and Creating a Marketplace for MSME Players " aims to assist and provide insight into the importance of digital marketing management for MSME actors in Pakunden Village and Turi Village, so they can understand how to manage their products on the marketplace properly and help empowered MSMEs to learn managing digital marketing through e-commerce applications to market their products easily. This activity was carried out in Pakunden Village and Turi Village, Sukorejo District, Blitar Regency. This socialization activity has succeeded in targeting the participants of the socialization activity which had been planned previously, while creating a marketplace for MSMEs, there are several MSMEs that we have chosen to empower. It shows that the socialization activities and the creation of this marketplace can be said to be successful.